A haplotype-like, chromosome-level assembled and annotated genome of Biomphalaria glabrata, an important intermediate host of schistosomiasis and the best studied model of schistosomiasis vector snails. - Daibin Zhong; Lijing Bu; Mohamed R Habib; Lijun Lu; Guiyun Yan; Si-Ming Zhang (Public Library of Science (PLoS), 2024)
Schistosomiasis is one of the world's most devastating parasitic diseases, afflicting 251 million people globally. The Neotropical snail Biomphalaria glabrata is an important intermediate host of the human blood fluke Schistosoma mansoni and a predominant model for schistosomiasis research. To fully exploit this model snail for biomedical research, here we report a haplotype-like, chromosome-level assembled and annotated genome of the homozygous iM line of B. glabrata that we developed at the University of New Mexico. Using multiple sequencing platforms, including Illumina, PacBio, and Omni-C sequencing, 18 sequence contact matrices representing 18 haploid chromosomes (2n = 36) were generated (337x genome coverage), and 96.5% of the scaffold sequences were anchored to the 18 chromosomes. Protein-coding genes (n = 34,559), non-coding RNAs (n = 2,406), and repetitive elements (42.52% of the genome) were predicted for the whole genome, and detailed annotations for individual chromosomes were also provided. Using this genomic resource, we have investigated the genomic structure and organization of the Toll-like receptor (TLR) and fibrinogen-domain containing protein (FReD) genes, the two important immune-related gene families. Notably, TLR-like genes are scattered on 13 chromosomes. In contrast, almost all (39 of 40) fibrinogen-related genes (FREPs) (immunoglobulin superfamily (IgSF) + fibrinogen (FBG)) are clustered within a 5-million nucleotide region on chromosome 13, yielding insight into mechanisms involved in the diversification of FREPs. This is the first genome of schistosomiasis vector snails that has been assembled at the chromosome level, annotated, and analyzed. It serves as a valuable resource for a deeper understanding of the biology of vector snails, especially Biomphalaria snails.